New Old Town in Elbląg – Multi-faceted Intervention in a Historic Area - Wiśniewska, Katarzyna (Protection of Cultural Heritage, 2021)
The purpose of this article is to review the principles of intervention in a historic area through a chronological presentation of the various concepts of reconstruction of the Old Town in Elbląg, as theoretical foundations for reconstruction, and to show changes in the approach to designing new buildings in a historic area. The consistent reconstruction of Elblag’s Old Town for nearly four decades has been theoretically grounded and adapted to the present day. By means of examples and defining phases of the reconstruction of the Old Town in Elblag, I would like to reflect on whether retroversion is a process that adapts itself each time to new contemporary needs, or rather retroversion as an authorial method ended in 2002 when the author stopped supervising projects and for nineteen years we have been simply observing the process of building the New Old Town.